The Pattern of Islamic Spiritual Guidance as an Effort to Prevent Radicalism Among Students of MAS Abnaulkhairat Lakea - Fajriani, Fajriani; Yani , Ahmad (The Future of Education Journal, 2024)
To prevent radicalism among students, collaboration from Islamic Religious Education (IRE) teachers, consisting of teachers of Qur'an-Hadith, Aqeedah-Akhlaq, and Fiqh in schools, is essential. This is because they are among the key parties responsible for providing a comprehensive understanding of Islamic teachings to students. IRE teachers should not teach intolerant attitudes, whether toward fellow Muslims or to people of other religions outside the school environment. Gentle behavior, mutual respect, and deliberation must always be prioritized. Madrasah Aliyah Swasta Abnaulkhairaat Lakea is one of the schools that encourages students to actively participate in religious activities at school. This study examines the pattern of religious spiritual guidance by IRE teachers as an effort to prevent radicalism among the students of Madrasah Aliyah Swasta Abnaulkhairaat Lakea. This research is a descriptive qualitative study. In data collection, the researcher uses methods of observation, interviews, and documentation. The main data sources for this study are IRE teachers (including teachers of Qur'an-Hadith, Aqeedah-Akhlaq, and Fiqh), the school principal, and students of MAS Abnaulkhairaat Lakea. As for the additional data sources, the researcher uses books, articles, and journals related to the pattern of religious spiritual guidance by IRE teachers as an effort to prevent radicalism among students. The data is analyzed qualitatively using techniques such as data reduction, data display, and conclusion drawing (verification).